Norma dan Integrasi Sosial: Studi Perbandingan Film AADC dan Film Dilan 1990 Sudut Pandang Durkheim - Humaira, Viona; Dewi, Trie Utari (Universitas Galuh, 2024)
This research aims to compare the depiction of the norms contained in social interactions and how this can influence social stability or change in the two films. This research method uses a qualitative descriptive method with a literary sociology approach from Durkheim's perspective. The results of this research are that the two films depict social dynamics, relationships between individuals, as well as the norms and values that govern their behavior. Both show that social factors, such as values, norms, and interactions between individuals, play an important role in shaping human character and actions. These films also reflect the complexity of social relationships and the importance of understanding social context to understand individual behavior.